2017
DOI: 10.25115/ejrep.v7i18.1369
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Load Theory: An Empirical Study of Anxiety and Task Performance in Language Learning

Abstract: Introduction. This study explores the relationship among three variables-cognitive load,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 32 publications
1
44
1
5
Order By: Relevance
“…Findings of present study did not fully support the results of study from Chen and Chang [5]. In the study, Chen and Chang showed that anxiety positively predict cognitive load which was assessed as a single construct.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Findings of present study did not fully support the results of study from Chen and Chang [5]. In the study, Chen and Chang showed that anxiety positively predict cognitive load which was assessed as a single construct.…”
Section: Discussioncontrasting
confidence: 99%
“…The finding of a study from Chen and Chang [5] in English learning context showed that anxiety positively predicted cognitive load. The other studies from Fraser, Ma, Teteris, Baxter, Wright, and McLoughlin [6] indicated that positive emotions had negative prediction on cognitive load, whereas negative emotions had positive prediction on cognitive load.…”
Section: Introductionmentioning
confidence: 96%
“…Both anxiety and cognitive load are inversely correlated with performance because both factors consume the working memory's processing resources (Chen and Chang 2009). Ashcraft and Kirk (2001) investigated this concept and found that the aspects of mathematics performance that rely heavily on working memory are the same aspects that are most affected by mathematics anxiety.…”
Section: Review Of Literaturementioning
confidence: 99%
“…It interferes with cognitive channels (Castillejo 2018) and decreases foreign language achievement (Onwuegbuzie, Bailey, and Daley 2000). It increases cognitive load and overwhelms working memory (Chen and Chang 2009). Anxious learners shift their cognition from the learning to the threat (Pappamihiel 2002), which obstructs cognitive processes and reduces performance (Maclntyre and Gardner 1994).…”
Section: Introductionmentioning
confidence: 99%